Model-Model Pengembangan Kurikulum - Ramadan, Fariz; Arawan, Arawan; Fatmawati, Fatmawati; Yennizar, Yennizar; Latif , Mukhtar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Curriculum development is a dynamic process that reflects changes in community needs, developments in science, and the demands of globalization. Various curriculum development models have been developed to respond to this complexity, ranging from linear to non-linear models, as well as top-down and bottom-up approaches. Each model has advantages and limitations depending on the context of its application, such as socio-cultural conditions, education policies, and resource capacity. This study aims to critically analyze various curriculum development models that have been developed by experts, including the Tyler, Taba, Olivia models. This analysis shows that there is no one universal model; the effectiveness of a model depends heavily on the ability to adapt to the context and the active participation of education stakeholders. Therefore, curriculum development should ideally be adaptive, collaborative, and oriented towards the sustainability of education quality. These findings emphasize the importance of a reflective and critical approach in selecting and implementing curriculum development models in order to produce relevant, inclusive, and transformative learning.